Mystik- Metapher- Bild Beiträge des VII. Makarios-Symposiums Göttingen 2007 - Tamcke, Martin (Universitätsverlag Göttingen, 2008)
German and Finnish theologians discuss the basic questions of Christian mysticism based on authors from the Orient. These authors from the Iraqi-Iranian sphere (Aphrahat the Persian manner, Babai the Great, St. Hierotheos, Isaac of Nineveh, Makarios), play a crucial role in the field of Christian-Oriental mysticism. At the same time they take contributions also beyond this geographic area and go to the mysticism in the German context after Luther (Brandt, Kant) and provide a review, a critical voice to the concept of mysticism and its positioning in the German theology.